1987
DOI: 10.1103/physrevd.36.1385
|View full text |Cite
|
Sign up to set email alerts
|

Comprehensive analysis of data pertaining to the weak neutral current and the intermediate-vector-boson masses

Abstract: The results of a comprehensive analysis of existing data on the weak neutral current and the W and Z masses are presented. The principal results are the following. (a) There is no evidence for any deviation from the standard model. (b) A global fit to all data yields sin 0~= 1 -Mgr /Mz =0.230+0.0048, where this error and all others given here include full statistical, systematic, and theoretical uncertainties (computed assuming three fermion families, m, & 100 GeV, and MH & 1 TeV). (c) Allowing p=M~/(Mz cos'0… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
242
0

Year Published

1990
1990
2013
2013

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 560 publications
(250 citation statements)
references
References 133 publications
6
242
0
Order By: Relevance
“…Alberto has played a unique and indispensable role in the development and testing of the standard model and of renormalizable gauge field theories. My one major collaboration with Alberto [3] was one of the most pleasant of my career. Happy birthday Alberto!…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Alberto has played a unique and indispensable role in the development and testing of the standard model and of renormalizable gauge field theories. My one major collaboration with Alberto [3] was one of the most pleasant of my career. Happy birthday Alberto!…”
Section: Discussionmentioning
confidence: 99%
“…It was found that ordinary SU (5) was excluded (consistent with the non-observation of proton decay), but that the supersymmetric extension was allowed, i.e., that the data was "consistent with SUSY GUTS and perhaps even the first harbinger of supersymmetry" [3].…”
Section: Historical Perspectivementioning
confidence: 91%
See 1 more Smart Citation
“…Sleptons in the intermediate states couple to gauginos and leptons via the modes listed in Table I. Thus, when the LSP is dominated by bino (which is what happens in most of the parameter space [6]), a prime signature of a Uð1Þ 0 extension of the MSSM is the reduction of purely hadronic events originating from the decays (22) and a corresponding enhancement of the leptonic events via the decays (25) and (26). While the rates of these decays and the depletion in the number of purely hadronic events depend on the masses and couplings of the intermediate sparticles in the cascades, the leptonic final states stemming from the right-handed squarks should offer sufficiently clean signatures to establish the existence of a Uð1Þ 0 extension at the LHC.…”
Section: Uð1þ 0 Effects Through Gauge and Higgs Fermionsmentioning
confidence: 99%
“…or tetraleptons (26) in the final state. Sleptons in the intermediate states couple to gauginos and leptons via the modes listed in Table I.…”
Section: Uð1þ 0 Effects Through Gauge and Higgs Fermionsmentioning
confidence: 99%